Digital Transformation Pressure, Techno-Stress, and Creative Performance: The Moderating Role of Digital Leadership - Wawat Hermawati; Mahfud Mahfud; Bagas Taqwa; Evy Oktaviani Fauzi Astuti (Politeknik Siber Cerdika Internasional, 2026)
Background: Digital transformation has become a strategic imperative for organizations operating in volatile and uncertain environments. However, this transformation simultaneously generates significant psychological demands on employees, particularly in the form of techno-stress. While prior research has examined digital transformation and employee outcomes separately, limited attention has been given to the mechanism through which digital transformation pressure impairs employee creative performance, and whether digital leadership can serve as a protective moderating factor. Objective: Drawing on Conservation of Resources (COR) Theory, this quantitative study examines the mediating role of techno-stress in the relationship between digital transformation pressure and employee creative performance, and the moderating role of digital leadership. Methods: We collected data from 385 employees across private-sector organizations in West Java, Indonesia, via a two-wave online survey. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for hypothesis testing. Results: Findings confirm that: (1) digital transformation pressure positively predicts techno-stress; (2) techno-stress negatively affects creative performance; (3) techno-stress fully mediates the relationship between digital transformation pressure and creative performance; and (4) digital leadership significantly moderates the indirect effect, attenuating the negative impact of techno-stress on creative performance. Conclusion: This study provides empirical evidence that digital leadership serves as a critical organizational resource that mitigates the negative impact of digital transformation pressure on employee creative performance through techno-stress. The findings highlight the importance of strengthening digital leadership competencies to sustain employee creativity during digital transformation while extending the application of Conservation of Resources (COR) Theory in the context of a rapidly digitalizing developing economy.